Emerging Trends of MXene Nanocomposites in Textile Substrates for Enhanced EMI Shielding: A Systematic Review - Nazish Saleem Abbas; Muhammad Haris Jamil; Nayab Ariff; Hamid Sharif; Peiguang Yan (Advanced Materials Interfaces)
Abstract Electromagnetic interference (EMI) shielding represents a critical technological challenge demanding innovative materials with superior performance characteristics. This comprehensive review systematically explores MXene nanomaterials as a transformative EMI shielding solution, critically analyzing traditional nanomaterial approaches and evaluating MXene's unique properties. The review comprehensively examines MXene's integration into textile substrates through advanced fabrication methodologies, including vacuum filtration, coating and dipping, spray coating, and spin coating techniques. A rigorous assessment of performance metrics encompasses electromagnetic shielding effectiveness, material thickness, electrical conductivity, mechanical properties, surface functionalization, durability, and application‐specific performance characteristics. This work examines how MXenes (Ti3C2), with their exceptional conductivity and ease of textile application, can be coupled with other nanomaterials such as graphite, carbon nanotubes (CNT), polyaniline (PANI), and silver nanowires (AgNWs) to improve EMI shielding effectiveness. A comprehensive list of MXene‐based hybrid nanomaterials offers materials scientists and engineers with an important reference framework for understanding and optimizing EMI shielding solutions. Finally, despite underlining MXene's enormous potential, this paper critically states existing constraints, such as nanomaterial dispersion, environmental stability, and production processes. This in‐depth review not only highlights recent achievements in MXene‐based textile composites but also indicates areas where more research is required to solve existing constraints and limitations.